The role of sensitization to aeroallergens and its determination in children with asthma in Ukraine - O.V. Mozyrska; Ya.V. Socolova (Сучасна педіатрія: Україна)
Asthma is a very common respiratory disease in the world. In particular, asthma has a great impact on the health of children. In this study, the distribution of sensitization among children with asthma has been analyzed.